Nucleofection disrupts tight junction fence function to alter membrane polarity of renal epithelial cells - Mo, Di (American Physiological Society, 2010)
Here, we compared the effects of nucleofection and lipid-based approaches to introduce siRNA duplexes on the subsequent development of membrane polarity in kidney cells. Nucleofection of Madin-Darby canine kidney (MDCK) cells, even with control siRNA duplexes, disrupted the initial surface polarity as well as the steady-state distribution of membrane proteins. Transfection using lipofectamine yielded slightly less efficient knockdown but did not disrupt membrane polarity. Polarized secretion was unaffected by nucleofection, suggesting a selective defect in the development of membrane polarity. Cilia frequency and length were not altered by nucleofection. However, the basolateral appearance of a fluorescent lipid tracer added to the apical surface of nucleofected cells was dramatically enhanced relative to untransfected controls or lipofectamine-treated cells. In contrast, [(3)H]inulin diffusion and transepithelial electrical resistance were not altered in nucleofected cells compared with untransfected ones. We conclude that nucleofection selectively hinders development of the tight junction fence function in MDCK cells.